Vitamin D Supplementation Improves Mitochondrial Function and Reduces Inflammation in Placentae of Obese Women - Phillips, Elysse A.; Hendricks, Nora; Bucher, Matthew; Maloyan, Alina (Frontiers in Endocrinology, 2022)
Background About 30% of women entering pregnancy in the US are obese. We have previously reported mitochondrial dysregulation and increased inflammation in the placentae of obese women. Vitamin D (VitD) is a major player in calcium uptake and was shown to modulate mitochondrial respiration and the immune/inflammation system. Studies show decreased VitD levels in obese individuals; however, the effect of maternal obesity on VitD metabolism and its association with placental function remains understudied. Methods Maternal and cord blood plasma and placental samples were collected upon C-section from normal-weight (NW, body mass index [BMI]<25) and obese (OB, BMI>30) women with uncomplicated pregnancies at term. We measured 25(OH)D3 (calcidiol) levels in maternal and cord blood plasma using ELISA. We assessed the expression of CYP27B1, an activator of calcidiol, and Vitamin D receptor (VDR) in placentae from NW and OB, and women with gestational diabetes and preeclampsia. In addition, we examined the effects of VitD supplementation on mitochondrial function and inflammation in trophoblasts from NW and OB, using the Seahorse Bioanalyzer and Western blot, respectively. Results Vitamin D levels in blood from OB but not NW women and in cord blood from babies born to NW and OB women showed a significant inverse correlation with maternal pre-pregnancy BMI (r=-0.50, p<0.1 and r=-0.55, p=0.004 respectively). Cord plasma VitD levels showed a positive correlation with placental efficiency, i.e., the ratio between fetal and placental weight, as well as with maternal blood VitD levels (r=0.69 and 0.83 respectively, p<0.00). While we found no changes in CYP27B1 in OB vs. NW women, VDR expression were decreased by 50% (p<0.03) independent of fetal sex. No changes in VDR expression relative to BMI-matched controls were observed in the placentae of women with gestational diabetes or preeclampsia. Cytotrophoblasts isolated from placentae of OB women showed a dose-dependent increase in VDR expression after 24-hour treatment with calcitriol (10 nM and 100 nM), an active form of VitD. Trophoblasts isolated from OB women and treated with calcitriol improved mitochondrial respiration (p<0.05). We also found a two-fold increase in expression of the NLRP3 inflammasome and the pro-inflammatory cytokine IL-18 in trophoblasts isolated from placentae of OB women (p<0.05), with IL-18 expression being reversed by calcitriol treatment (100 nM). Conclusions We show that VitD deficiency is at least partially responsible for mitochondrial dysfunction and increased inflammation in the placentae of obese women. Vitamin D supplementation could be beneficial in improving placental dysfunction seen in obese women.